Molecular characterisation of six patients with prolidase deficiency: identification of the first small duplication in the prolidase gene and of a mutation generating symptomatic and asymptomatic outcomes within the same family - ELÇİOĞLU, HURİYE NURSEL (BMJ PUBLISHING GROUP, 2006)
Prolidase deficiency (PD) is a rare autosomal recessive connective tissue disorder caused by mutations in the prolidase gene. The PD patients show a wide range of clinical outcomes characterised mainly by intractable skin ulcers, mental retardation and recurrent respiratory infections. Here we describe five different PEPD mutations in six European patients. We identified two new PEPD mutant alleles: a 13 bp duplication in exon 8, which is the first reported duplication in the prolidase gene and a point mutation resulting in a change in amino acid E412, a highly conserved residue among different species. The E412K substitution is responsible for the first reported phenotypic variability within a family with severe and asymptomatic outcomes.
Keywords: PYROCOCCUS-FURIOSUS; NONSENSE MUTATION; CLINICAL SYMPTOMS; PEPD GENE; PURIFICATION; POLYPEPTIDE; ENZYME; FIBROBLASTS; ERYTHROCYTE; EXPRESSION